Hepatitis B virus-associated hepatocellular carcinoma in South Africa: epidemiology and impact of HIV-1 co-infection and immune dysregulation - Maponga, Tongai Gibson (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016